OVERWEIGHT DAN PREMESNTRUAL SYNDROME - Irma Hamdayani Pasaribu; Maria Alia Rahayu; Rina Marlina (HSG (Health Science Growth) Journal, 2022)
Premenstrual syndrome is identified by physical, emotional, and behavioral symptoms that greatly affect a woman's daily life, including work and daily activities, which appear before menstruation and end spontaneously a few days after menstruation. The exact cause of premenstrual syndrome is not known, but it may be due to hormonal changes, prostaglandins, diet, medications, and lifestyle. Women who are overweight are at high risk of developing PMS. This study is a descriptive study with a cross-sectional approach to determine the relationship between overweight and premenstrual syndrome. The study sample was 53 midwifery student class 2019-2020 with inclusion criteria have regular menstrual cycles in the last two months, willing to be respondents and filling out the informed consent form. The independent variable in this study is Body Mass Index (BMI) and the dependent variable is PMS. BMI is obtained by calculating the formula BMI=Weight: Height (m)2. To find out the presence of PMS using the Shortened Premenstrual Assessment Form (SPAF) questionnaire. From the results of the Chi Square statistical test obtained P-Value 0.00 and OR 8.02, it can be concluded that overweight is associated with Premenstrual Syndrome. Keywords: Nutritional Status, Overweight, Premenstrual Syndrome